Plant–plant facilitation increases with reduced phylogenetic relatedness along an elevation gradient. Issue 2 (20th November 2020) - Duarte, Milen; Verdú, Miguel; Cavieres, Lohengrin A.; Bustamante, Ramiro O.
Abstract : Environmental conditions can modify the intensity and sign of ecological interactions. The stress gradient hypothesis (SGH) predicts that facilitation becomes more important than competition under stressful conditions. To properly test this hypothesis, it is necessary to account for all (not a subset of) interactions occurring in the communities and consider that species do not interact at random but following a specific pattern. We aim to assess elevational changes in facilitation, in terms of species richness, frequency and intensity of the interaction as a function of the evolutionary relatedness between nurses and their associated species. We sampled nurse and their facilitated plant species in two 1000–2000 m. elevation gradients in Mediterranean Chile where low temperature imposes a mortality filter on seedlings. We first estimated the relative importance of facilitation as a mechanism adding new species to communities distributed along these gradients. We then tested whether the frequency and intensity of facilitation increases with elevation, taking into account the evolutionary relatedness of the nurse species and the facilitated species. We found that nurses increase the species richness of the community by up to 35%. Facilitative interactions are more frequent than competitive interactions (56% versus 44%) and facilitation intensity increased with elevation for interactions involving distantly related lineages. Our results highlight the importance of including an evolutionary dimension in the study of facilitation to have a clearer picture of the mechanisms enabling species to coexist and survive under stressful conditions. This knowledge is especially relevant to conserve vulnerable and threatened communities facing new climate scenarios, such as those located in Mediterranean‐type ecosystems.